ANALISIS PENGENDALIAN KUALITAS PRODUK KALENG SARDEN DENGAN MENGGUNAKAN SEVEN TOOLS - ., Samsuri; Dwilaksana, Dedi; Sidartawan, Robertus; Darsin, Mahros; Dwi Hidayatul Qoryah, Rika (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
Quality control is an activity to rise of quality is expected, through feedback on product characteristics and implementation of improvements if there are deviation. Quality control is used by companies that produce product (manufacturing) as a tool to minimize defective products so they can satisfied the quality is set by the company and satisfy consumers. However, the reality in the field is not expected and many defective products are found that are not in accordance with the standards. This study purposes to determine how the implementation of quality control uses seven tools in an effort to control defective product in the Pacific Harvest company. Droop defects has the greatest contribution in product defects to sardine production, which is a human and machine factor. The factors that caused of product defects are human, machine, material, method and environment. The results of the analysis using the control chart p there are 1 of 16 points above UCL is data 13. Then revisions and recalculated there are found 1 of 15 points above UCL is data 14. Then revisions and improvements of data are carried out until all points are within the boundary control. Problem solving using causal diagrams (fishbone diagram) to identify causes of defects and then provide solutions.